Tuberculosis and Leprosy Co-Infection: A Perspective on Diagnosis and Treatment. (4th October 2017) - Kilpatrick, Dustin; Sampath, Rahul; Jones, Allison; Movaghar, Sarah; Kelly, Rachel; Costic, Donald
Abstract: Background: The Marshall Islands are known to be endemic for both leprosy and tuberculosis (TB). Active TB needs to be ruled out in all cases of leprosy, as treatment will lead to rifampin monotherapy of undiagnosed TB co-infection. The use of protein based interferon gamma release assays (IGRAS) to test for latent TB in leprosy endemic areas is confounded by the crossreactivity of T-cell response to the antigenic homologs of these proteins in Mycobacterium leparae. Methods: The Purified Protein Derivative (PPD) skin test may have some utility in the diagnosis of latent TB in the setting of paucibacillary leprosy, however "giant reactions" to PPD testing have been documented in monoinfection with multibacillary leprosy. Results: A 32-year-old Marshallese woman presented to the surgical department with symptoms concerning for osteomyelitis of the third distal phalanx, multiple burn wounds on both hands, and hypoaesthetic- hypopigmented skin lesions. She was referred to the National Hansen's institute where a limited disarticulation of the distal phalanx and a slit skin biopsy was performed. Fite stain was negative, but PCR was positive for Mycobacterium leprae. The patient also had a strongly positive IGRA test for TB, and a positive PPD skin test. A chest x-ray showed a subtle infiltrate in the right middle lobe, three induced sputa were AFB negative by smear - however 1/3 was culture positive for drug-susceptible TB. The patient then underwent standard drug therapy for TB with the addition of dapsone for the treatment of Hanson's. Repeat sputum cultures were negative at one month, and the patient had improvement in her skin hypopigmentation within four months of therapy. Conclusion: The immunological milieu of the host appears to paradoxically influence susceptibility to mycobacterial coinfection, with no consensus regarding whether prior exposure to one offers protection or predisposition to the other. The clinical implications of failure to identify active TB in a case of leprosy can not be understated, and positive IGRA or PPD testing in leprosy should not be considered falsely positive without further investigation. If treatment for paucibacillary leprosy is to be considered before ruling out active TB then minocycline may temporarily replace Rifampin. Disclosures: All authors: No reported disclosures.